Analisis Pengaruh Biaya Bahan Baku Biaya Tenaga Kerja Terhadap Harga Pokok Prouksi Usaha Tenun Songket Di Desa Kiraman Kecamatan Alor Selatan Kabupaten Alor - Banamakani, Belandina; Tang, Sefnat Aristarkus; Sabu, Junius Menase Sau; Maro, Yustina (Jurnal Ilmiah Wahana Pendidikan, 2023)
The cost of production is all costs incurred to produce goods or services that will be sold during the period in question. The cost of production is an important element to assess the success of a trading or manufacturing company. The cost of production has a close relationship with indicators of the company's success, such as sales gross profit and net profit. This study aims to determine the effect of raw material costs on the cost of production of songket weaving businesses in Kiraman Village, South Alor District, Alor Regency; to determine the effect of labor costs on the cost of production of the songket weaving business in Kiraman Village, South Alor District, Alor Regency; and to determine the effect of raw material costs and labor costs on the cost of production of songket weaving businesses in Kiraman Village, South Alor District, Alor Regency. This research is a quantitative study using secondary data obtained from the financial data of songket weaving craftsmen in Kiraman Village, South Alor District, Alor Regency. Data collection was carried out using observation, interviews and documentation while data analysis used descriptive statistics, classical assumption tests and multiple linear regression. Hypothesis testing is done using a partial test or t test and simultaneous test or F test. The results showed that partially the cost of raw materials had a positive and significant effect on the cost of production of the songket weaving business in Kiraman Village, South Alor District, Alor Regency, as evidenced by a probability value of 0.000; partially labor costs have a positive and significant effect on the cost of production of the songket weaving business in Kiraman Village, Alor Selatan District, Alor Regency as evidenced by a probability value of 0.000; and simultaneously raw material costs and labor costs have a positive and significant effect on the cost of production of the songket weaving business in Kiraman Village, South Alor District, Alor Regency, as evidenced by the probability value of the F test of 0.000.